Analisis Unsur Intrinsik Tokoh Dan Penokohan Roronoa Zoro Pada Komik One Piece - Aritonang, Yosua; Arfianty, Rani (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
This article focuses on the One Piece comic by Oda Eiichiro. This fictional comic was created in 1997 and made into anime in 1999, telling the adventures of a man who wants to become a pirate king named Monkey D Luffy. To achieve his goal, he recruited ten members. This research discusses the intrinsic elements of the character and characterization of Roronoa Zoro. The research uses qualitative methods which produce descriptive data in the form of written words. Analysis result shows that the character Roronoa Zoro is a deputy ship captain who is very loyal to his captain and is willing to sacrifice his life for his captain. However, the character Roronoa Zoro has a dark past because he doesn't know who and where his parents are. The character Roronoa Zoro experiences a change in character from being silent and gloomy and easily carried away by emotions to being responsible, loyal and nurturing to his fellow members. So the character Roronoa Zoro is classified as a developing character.